Desialylation of platelets induced by Von Willebrand Factor is a novel mechanism of platelet clearance in dengue - Silvita Fitri Riswari; Rahajeng N. Tunjungputri; Vesla Kullaya; Fadel Muhammad Garishah; Gloria S. R. Utari; Nur Farhanah; Gijs J. Overheul; Bachti Alisjahbana; Muhammad Hussein Gasem; Rolf T. Urbanus; Philip G. de Groot; Dirk J. Lefeber; et al. (2019)
Thrombocytopenia and platelet dysfunction are commonly observed in patients with dengue virus (DENV) infection and may contribute to complications such as bleeding and plasma leakage. The etiology of dengue-associated thrombocytopenia is multifactorial and includes increased platelet clearance. The binding of the coagulation protein von Willebrand factor (VWF) to the platelet membrane and removal of sialic acid (desialylation) are two well-known mechanisms of platelet clearance, but whether these conditions also contribute to thrombocytopenia in dengue infection is unknown. In two observational cohort studies in Bandung and Jepara, Indonesia, we show that adult patients with dengue not only had higher plasma concentrations of plasma VWF antigen and active VWF, but that circulating platelets had also bound more VWF to their membrane. The amount of platelet-VWF binding correlated well with platelet count. Furthermore, sialic acid levels in dengue patients were significantly reduced as assessed by the binding of Sambucus nigra lectin (SNA) and Maackia amurensis lectin II (MAL-II) to platelets. Sialic acid on the platelet membrane is neuraminidase-labile, but dengue virus has no known neuraminidase activity. Indeed, no detectable activity of neuraminidase was present in plasma of dengue patients and no desialylation was found of plasma transferrin. Platelet sialylation was also not altered by in vitro exposure of platelets to DENV nonstructural protein 1 or cultured DENV. In contrast, induction of binding of VWF to glycoprotein 1b on platelets using the VWF-activating protein ristocetin resulted in the removal of platelet sialic acid by translocation of platelet neuraminidase to the platelet surface. The neuraminidase inhibitor oseltamivir reduced VWF-induced platelet desialylation. Our data demonstrate that excessive binding of VWF to platelets in dengue results in neuraminidase-mediated platelet desialylation and platelet clearance. Oseltamivir might be a novel treatment option for severe thrombocytopenia in dengue infection.